2022
DOI: 10.1007/s11154-022-09714-z
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition management of hospitalized patients with diabetes/hyperglycemia and COVID-19 infection

Abstract: Diabetes mellitus and/or hyperglycemia are highly prevalent medical conditions in patients hospitalized for coronavirus disease 2019 (COVID-19) and are associated with adverse outcomes. In addition, COVID-19 itself can provoke fluctuating and high glucose levels that can be difficult to manage upon hospitalization. Hospitalized patients with COVID-19 are at high risk of malnutrition due to an increase in nutritional requirements and a severe acute inflammatory response. The management of patients with diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…Both lymphocyte function and innate host defense mechanisms (macrophages and granulocytes) are affected [ 50 ]. Second, malnutrition not only promotes acute and chronic infections, but also leads to increased food intake, nutrient absorption, direct or catabolic nutrient losses, and metabolic demands [ 13 , 51 ]. Under inflammatory conditions, mediators increase the catabolic disease state, characterized by enhanced arginine use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both lymphocyte function and innate host defense mechanisms (macrophages and granulocytes) are affected [ 50 ]. Second, malnutrition not only promotes acute and chronic infections, but also leads to increased food intake, nutrient absorption, direct or catabolic nutrient losses, and metabolic demands [ 13 , 51 ]. Under inflammatory conditions, mediators increase the catabolic disease state, characterized by enhanced arginine use.…”
Section: Discussionmentioning
confidence: 99%
“…Both diabetes and malnutrition affect the subjective quality of life and the incidence of complications as well as life expectancy in hospitalized patients [ 11 , 12 ]. Patients with diabetes usually are at high risk of malnutrition due to increased nutritional requirements and severe acute inflammatory response [ 13 ]. It has been shown that malnutrition is associated with significant modulation of glycemic, hormonal, and cytokine parameters in type 2 diabetes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Undernourished patients are more susceptible to infection with SARS-CoV-2. Also, COVID-19 itself can lead to malnutrition, which affects outcome and prognosis; therefore, COVID-19 outcome could be improved with improved nutritional status[ 58 ].…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Population-level malnutrition is associated with increased rates of fatal COVID-19 in areas where undernutrition is commonplace (58). Moreover, nutritional status is adversely affected by acute and chronic infections, which serve as negative prognosticators, especially in institutional settings (59)(60)(61). Patients with COVID-19 are especially vulnerable to the metabolic derangements associated with malnutrition, particularly in light of the significant inflammatory response that accompanies both conditions (62)(63)(64).…”
Section: Edge 2: Covid-19 and Malnutrition Epidemiologymentioning
confidence: 99%